Price and corporate social responsibility: The consumers’ perspective - Real, Elizabeth (2014)
The author performs a systematic literature review on academic papers regarding Corporate Social Responsibility and Price, from the consumer’s perspective, in ISI Current Contents. Based on 219 academic papers a content analysis is undertaken in a grounded-theory methodological approach. A growing trend of publications from 2008 onwards, revealing the relationship of CSR and price as an emerging concern, is presented and specialized international journals in the area are pointed out. A map of the field allows the identification of main research areas, emphasizing possible trends towards publications in this field in the upcoming years. The main topics reflected in each group are CSR perceptions and its relation with purchase intention (group 1), how CSR drives consumer behavior, namely consumer involvement and engagement (group 2), the ethical dimension of CSR and its impact on consumer response, namely the willingness to pay a higher price (group 3), and finally, the case of cause-related marketing approach (group 4), which may represent a specific form of CSR, allowing companies to boost their reputation and set up higher prices.